The Aleppo Codex [compact disc, unabridged] : a true story of obsession, faith, and the pursuit of an ancient Bible - Friedman, Matti. 1977- (HighBridge Audio, 2012)
This true-life detective story unveils the journey of a sacred text-- the tenth-century annotated bible known as the Aleppo Codex-- from its hiding place in a Syrian synagogue to the newly founded state of Israel.